Session RPE and stress tolerance in young volleyball and basketball players - Alexandre Moreira; Camila Gobo de Freitas; Fábio Yuzo Nakamura; Marcelo Saldanha Aoki (Universidade Federal de Santa Catarina, 2010)
The present study investigated the effect of training load distribution on the perceivedsources and symptoms of stress during 6 weeks of sports training in young athletes. The sessionRPE method and the DALDA questionnaire were used to assess internal training load and stresstolerance. Twenty young men athletes participated in this study. Repeated measures ANOVArevealed higher training loads in the first and second weeks of training (p<0.05). Interestingly,increased symptoms of stress were also observed in the first two weeks of training, with a similartendency for sources of stress when the group was analyzed as a whole. A significant increasein the "worse than normal" answers in part B of the DALDA questionnaire (symptoms ofstress) was observed for the subgroup submitted to a higher training load (>400 AU) (two-wayANOVA, p<0.05). The present findings support the hypothesis that the internal training load(session RPE) affects stress tolerance. These results emphasize the importance of regular trainingmonitoring in order to reduce the occurrence of deleterious adaptations and to optimize desiredadaptive responses.